Can we stop immunomodulatory treatments in secondary progressive multiple sclerosis?. (18th October 2016) - Bonenfant, J.; Bajeux, E.; Deburghgraeve, V.; Le Page, E.; Edan, G.; Kerbrat, A.
Abstract : Background and purpose: The benefits of immunomodulatory treatments in secondary progressive multiple sclerosis (SPMS) are unclear, calling into question their continuation. In the present observational study, we investigated the effect of treatment withdrawal on the clinical course of SPMS. Methods: We included 100 consecutive patients with SPMS who regularly attended our multiple sclerosis clinic. Inclusion criteria were (i) secondary progressive phenotype for at least 2 years, (ii) immunomodulatory treatment for at least 6 months and (iii) treatment stopped with no plans to switch to another. Clinical and magnetic resonance imaging (MRI) data before and after treatment discontinuation were assessed. Factors associated with relapses and/or MRI activity were identified. Results: Mean treatment duration was 60.4 ± 39.3 months, and mean follow‐up duration after treatment withdrawal was 62.4 ± 38.4 months. The annualized relapse rate remained stable at 1 and 3 years after treatment withdrawal [0.09, 95% confidence interval (CI), 0.05–0.17 and 0.07, 95% CI, 0.05–0.11, respectively], relative to the 3 years prior to treatment withdrawal (0.12, 95% CI, 0.09–0.16). Sixteen patients experienced a relapse and 19 had a gadolinium‐positive MRI scan without relapse during follow‐up. A gadolinium‐positive MRI scan within the previous 3 years before treatment withdrawal and Expanded Disability Status Scale score of <6 were positively associated with relapse and/or MRI activity after discontinuation ( P = 0.0004 and P = 0.03, respectively). Conclusion: In this retrospective study, including a limited number of patients with SPMS, the annualized relapse rate remained stable after treatment withdrawal, relative to before treatment withdrawal. Further prospective studies are needed to confirm this result and provide evidence‐based guidelines for daily practice. Abstract : Clickhere for the corresponding questions to this CME article.